Chaand apni shakal kyun bdalta hai? - Asimof Isak (Ferozesons; Pakistan, 2008)
Chaand Apni Shakal Kyun Badalta Hai? explores the scientific and poetic explanation of the moon's phases, blending curiosity with wonder.